2018
DOI: 10.29021/spdv.76.3.910
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologia das infeções fúngicas superficiais em Portugal - revisão de 3 anos (2014-2016)

Abstract: Introdução: As infeções fúngicas superficiais são as dermatoses infeciosas mais frequentes e a sua incidência continua a aumentar. Os dermatófitos são os principais agentes causais apresentando, contudo, uma distribuição geográfica variável.Material e Métodos: O presente estudo teve como objetivo a caracterização epidemiológica das infeções fúngicas superficiais diagnosticadas nos Serviços/Unidades de Dermatologia pertencentes ao Serviço Nacional de Saúde Português entre janeiro de 2014 e dezembro 2016 através… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
2
0
3
Order By: Relevance
“…From a mycological perspective, it is remarkable that T rubrum was the aetiologic agent in all cases of tinea barbae. Our data confirm and reinforce the recent 3‐year survey by Rato et al and Marques Pereira et al, which, in contrast to the northern regions of Portugal where tinea barbae is mostly caused by zoophilic species ( Microsporum canis , Trichophyton mentagrophytes var granulare , leveduriform fungi), in Lisbon, a major urban centre, the anthropophilic species such as T rubrum predominate. For instance, this geographic distinction is similar to the one found in adult tinea capitis.…”
Section: Discussionsupporting
confidence: 92%
“…From a mycological perspective, it is remarkable that T rubrum was the aetiologic agent in all cases of tinea barbae. Our data confirm and reinforce the recent 3‐year survey by Rato et al and Marques Pereira et al, which, in contrast to the northern regions of Portugal where tinea barbae is mostly caused by zoophilic species ( Microsporum canis , Trichophyton mentagrophytes var granulare , leveduriform fungi), in Lisbon, a major urban centre, the anthropophilic species such as T rubrum predominate. For instance, this geographic distinction is similar to the one found in adult tinea capitis.…”
Section: Discussionsupporting
confidence: 92%
“…11,13,15,16,[18][19][20] Em um estudo realizado em Portugal, T. rubrum foi a espécie mais frequente, com 53,6% dos isolamentos, seguido do M. audouinii e do T. mentagrophytes, respetivamente com 10,7% e 10,4% dos isolamentos. 22 Tanto o primeiro como o terceiro fungo mais frequente desse trabalho, corroboram com os achados do nosso estudo.…”
Section: Discussionunclassified
“…tonsurans como mais frequente 20. Em Portugal observou-se que o M. Audouinii foi o dermatófito mais frequentemente isolado em couro cabeludo (42,6% dos casos), seguido do T. Soudanense (22,1%), T. tonsurans (10,8%) e então M. Canis (10,5%) 22. Interroga-se o motivo dessa diferença de achados.…”
unclassified
“…National and international studies have found dermatophytes as the most commonly found etiologic agents in onychomycosis, being represented by the genera Trichophyton, Microsporum and Epidermophyton, followed by yeasts, represented mostly by the genus Candida, as well as by non-dermatophyte filamentous fungi, in which the Scopulariopsis, Fusarium and Aspergillus are the main genera [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%